O intertexto bíblico na literatura juvenil : As Crônicas de Nárnia, de C. S. Lewis - Gonçalves, Sabrina Rosa (2015)
Most of the literary texts classified as juvenile literature by the publishers are similar to each other when it comes to structure. These narratives usually present myths, organized constructions that depict human cyclic trajectories, which show characters as role models. Considering, therefore, the need to identify these dialogues among mythical works, this paper analyzes the short stories The magician s nephew , The lion, the witch and the wardrobe and The last battle , which compose The chronicles of Narnia, by C. S. Lewis and his biblical intertext as alternative for teenagers nowadays. Therefore, this research has three steps: the first one theorizes about intertext, based on studies of Julia Kristeva, Gérard Genette and Antoine Compagnon, and Bible as literature, from the point of view of Northrop Frye and Robert Alter; the second step, based on researches by Pierre Bourdieu, Roger Chartier and other experts in this area, ponders about the market of literary productions and brings an overview of The chronicles of Narnia, by Clive Staples Lewis, and the Bible; the third moment refers to the analysis of the intertext, considering that both have mythic structures, and to the validity of the works in question as role model for today's readers.